Single-Atom Catalysts for Hydrogen Evolution Reaction: The Role of Supports, Coordination Environments, and Synergistic Effects - Zhuoying Liang; Yu Zhang; Linli Liu; Miaolun Jiao; Chenliang Ye (Nanomaterials)
Single-atom catalysts (SACs) have emerged as highly promising catalytic materials for the hydrogen evolution reaction (HER), attributed to their maximal atomic utilization efficiency and unique electronic configurations. Many structure parameters can influence the catalytic performance of SACs for HER, and the intrinsic advantages of SACs for HER still need to be summarized. This review systematically summarizes recent advances in SACs for HER. It discusses various types of SACs (including those based on Pt, Co, Ru, Ni, Cu, and other metals) applied in HER, and elaborates the critical factors influencing catalytic performance—specifically, the supports, coordination environments, and synergistic effects of these SACs. Furthermore, current research challenges and future perspectives in this rapidly developing field are also outlined.